Identification of Learning Sources and Methods for Iranian Internet Entrepreneurs: Typology and Prioritization of Learning Methods - Ghanbar Mohamadi Elyasi; Reza Zaefarian; Bahareh Mafi (Journal of Information Technology Management)
Internet entrepreneurs methods for identification and use of knowledge, skills and insights related to their business, have major impacts on creation and effective management of such businesses. Due to the diversity of learning methods used by internet entrepreneurs, this article intended to identify and prioritize them. In order to do so, semi-structured interviews were conducted with 10 successful internet entrepreneurs and by means of coding method, conventional learning methods for internet entrepreneurs were identified. Then, by distribution and using Friedman analysis of 376 questionnaires, superior learning methods were prioritized. Findings of this study indicated four major sources of learning as follows: learning from teaching – publications, learning from work – task, learning from social-human interaction, and learning from imitation – benchmarking. Furthermore, learning methods prioritization results showed that observation and imitation of best websites, reading websites content, personal thoughts and initiatives of problem solutions are three main methods of learning for Iranian entrepreneurs.